Peningkatan Kesadaran Legalitas dalam Inovasi Pemasaran UMKM - Zaman, Jajang Saeful; Sobari, Hendi; Setya Wardhani, Dyah Ciptaning Lokiteswara; Sukandar, Erna Rusmiwati; Syarif, Endang; Makarim, Siti Amirah (Journal Pemberdayaan Masyarakat Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) have great potential to contribute to economic growth and job creation in various countries. In the ever-growing digital era, marketing innovation is the key to increasing the visibility and competitiveness of MSMEs. However, legal aspects in marketing innovation are often neglected, causing legal risks that can endanger the sustainability of MSME businesses. Through a community service approach, we can provide training and resources to MSMEs to help them understand and comply with relevant legal regulations. We also cover various legal aspects in marketing innovation, including copyright, trademarks, data privacy and taxation. With a better understanding of legality, MSMEs can develop marketing strategies that comply with the law, reduce risks, and create a strong foundation for their business growth. By collaborating, we can create an environment that supports legally responsible marketing innovation for MSMEs. Finally, increasing legality awareness in marketing innovation is expected to strengthen the competitiveness of MSMEs, support local economic growth, and provide a sustainable contribution to society and the economy.